Removal of Tetracycline Using Tungsten Disulfide/Graphene Oxide as Photocatalyst: Effect of Light Irradiation and Kinetic Studies - Zolekafeli, Zulhatiqah; Sateria, Syafarina Farisa; Mohamed, Ahmad Husaini; Alias, Siti Hajar; Sambasevam, Kavirajaa Pandian; Baharin, Siti Nor Atika (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2024)
Once widely utilised in both human and veterinary medicine, tetracycline antibiotics are now recognised as major environmental pollutants with detrimental effects on the environment and human health. Concerns regarding allergic responses, gastrointestinal problems, and diseases resistant to antibiotics are raised by their persistence in soil, groundwater, and surface water. The production of a tungsten disulfide-graphene oxide nanocomposite for tetracycline degradation under varied light sources is presented in this work. The successful incorporation of tungsten disulfide on graphene oxide structures was confirmed by characterization using Attenuated Total Reflectance-Fourier Transform Infrared Spectroscopy (ATR-FTIR) and X-ray Diffraction (XRD). This revealed characteristic peaks for hydroxyl (3328 cm–1), carbonyl (1732 cm–1), alkene (1583 cm–1), and ether (1044 cm–1) bonds, as well as sulphur bonding (500 to 739 cm–1). With a d-spacing of 2.24 nm, the tungsten disulphide-graphene oxide nanocomposite had a strong peak at 2θ = 15.5˚corresponds to the (002) plane, as shown by X-ray diffraction. A distinctive GO peak was found at 2θ = 10.1˚, which corresponds to the plane (002). With light emitting diodes (95.67%), fluorescent lights (81.28%), and ultraviolet-visible light (88.09%), the nanocomposite in a photoreactor showed excellent photocatalytic efficiency. The better performance of the tungsten disulfide-graphene oxide nanocomposite under varying illumination circumstances, as determined by the Langmuir-Hinshelwood (LH) model, presents a viable and sustainable option for tetracycline degradation in water purification. This technique tackles a long-term strategy for tetracycline photocatalytic degradation in water purification under different illumination scenarios. Copyright © 2024 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).